2013
DOI: 10.1111/jcpp.12169
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: The neurobehavioral development of multiple memory systems – implications for childhood and adolescent psychiatric disorders

Abstract: Extensive evidence indicates that mammalian memory is organized into multiple brains systems, including a “cognitive” memory system that depends upon the hippocampus and a stimulus-response “habit” memory system that depends upon the dorsolateral striatum. Dorsal striatal-dependent habit memory may in part influence the development and expression of some human psychopathologies, particularly those characterized by strong habit-like behavioral features. The present review considers this hypothesis as it pertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 283 publications
4
64
1
1
Order By: Relevance
“…This system is activated in tasks involving attention and inhibitory control, such as the Stroop (42, 43), Simon spatial incompatibility (4244), go/no-go (45), and continuous performance tasks (46). The third is a higher-order sensory/memory system comprising inferior and dorsal parietal cortex, posterior, inferior and middle temporal cortex, cuneus, and hippocampus (4750). …”
Section: Discussionmentioning
confidence: 99%
“…This system is activated in tasks involving attention and inhibitory control, such as the Stroop (42, 43), Simon spatial incompatibility (4244), go/no-go (45), and continuous performance tasks (46). The third is a higher-order sensory/memory system comprising inferior and dorsal parietal cortex, posterior, inferior and middle temporal cortex, cuneus, and hippocampus (4750). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, numerous investigators have suggested that enhancement of the dorsal striatum-dependent memory system might in part underlie the development of some neuropsychiatric disorders, in particular disorders with prominent habit-like behavioral features (White, 1996, Everitt and Robbins, 2005, Schwabe et al., 2011a, Berner and Marsh, 2014, Gillan and Robbins, 2014, Goodman et al., 2014, Goodman and Packard, 2016a, Goodman and Packard, 2016b). For instance, post-traumatic stress disorder (PTSD) is partly characterized by intractable avoidance behaviors that occur in response to trauma-related cues, and some investigators suggest that such avoidance symptoms may be a manifestation of enhanced DLS-dependent habit memory following very high levels of emotional arousal (i.e., trauma; Packard, 2009, Schwabe et al., 2010c, Goodman et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, motor impairments alone cannot explain the altered cognition and behavior in TS (Goodman et al, 2014;M. M. Robertson, 2015b).…”
mentioning
confidence: 99%
“…Interestingly, alterations of procedural memory have been proposed as one of the neurocognitive underpinnings of tics in TS (Goodman et al, 2014;Kéri et al, 2002; M. M. Robertson, 2015b). Moreover, procedural memory is an ideal avenue to study mental simulations, which play a role in various motor and cognitive processes (Barsalou, 2008).…”
mentioning
confidence: 99%